The Effect of Social Support with Depression in Chronic Kidney Failure Patients Treating Hemodialization - Almubarok, Allama Zaki; Permana, Iman (JOSING: Journal of Nursing and Health, 2022)
This study aims to identify the latest evidence-based on the effect of social support on depression in chronic renal failure patients undergoing hemodialysis. The research method used in this study is a literature review with a literature search using the electronic database CINAHL, PubMed, Pro Quest, Cochrane, Google Scholar, and Garuda. The results showed that the original sixteen articles met the inclusion criteria in 4 themes: social and family support that affects self-management and hope for progress, family support, emotional support, and appropriate and appropriate family support. In conclusion, all aspects of social and family license affect depression and anxiety in chronic kidney failure patients undergoing hemodialysis. Keywords: Depression, Social Support, Hemodialysis, End-Stage Kidney Disease